MEMPERGILIRKAN HARTA WARISAN DI NAGARI TARAM PRESPEKTIF HUKUM ISLAM - Ramadhani Ramadhani; Zainuddin Zainuddin (Institut Agama Islam Negeri Batusangkar, 2022)
This study examines the distribution of inheritance in rotation. The problem is that the inheritance is not distributed individually to the heirs, but the heirs only take the proceeds from the inheritance, and if the male heir dies, the right of turn is removed, but if the female heir dies, the right of turn is continued by his son. From these problems, questions arise about how the process of implementing the rotation of inheritance in Nagari Taram is and how to review Islamic aristocratic law on the implementation of rotation of inheritance. This research is a field research. The data were obtained through interviews with respondents and documents of inheritance, then the data were narrated descriptively. The results are discussed with the proposed theories. This study found that the rotation of inheritance is a community tradition that has been going on for quite a long time, the types of assets that are rotated are rice fields, gardens, and livestock (cows). Based on Islamic inheritance law, rotating inheritance in Nagari Taram is not in accordance with the provisions of Islamic inheritance contained in Surah An-Nisa 'verse 11-12 and the principles in Islamic inheritance law. This verse explains that inheritance must be distributed according to the share of each heir, while the tradition of rotating inheritance in Nagari Taram the heirs do not know how much each heir is entitled to receive. And children of heirs who have died are not entitled to a turn, because grandchildren are veiled by children.